Study on mussel-inspired tough TA/PANI@CNCs nanocomposite hydrogels with superior self-healing and self-adhesive properties for strain sensors. (15th November 2020) - Yan, Qiming; Zhou, Meng; Fu, Heqing
Abstract: Tough, self-adhesive and conductive hydrogels have recently attracted considerable interest due to their promising applications in electronic skins, wearable devices and flexible sensors. In this work, we designed a mussel-inspired nanocomposite hydrogel derived from water-soluble tannic acid/polyaniline coated cellulose nanocrystals (TA/PANI@CNCs) and various functional acrylic monomers. The incorporated TA/PANI@CNCs not only endowed the nanocomposite hydrogels with enhanced electrical conductive network and mechanical performance, but also played an important role in repeatable and durable adhesiveness to human skin without additional fixation. By taking the advantage of double networks based on various supramolecular interactions and dynamic borate ester bonds, the hydrogels exhibited a dramatic breaking strain of 974%, fracture stress of 759 kPa and rapid self-healing ability at room temperature without external stimuli. In addition, the as-prepared nanocomposite hydrogels had great strain sensitivity and excellent electrical conductivity, which can be employed as flexible strain sensors for tracking human body motion with a broad range of strain or directly assembled on other materials surfaces as electrical circuits. Compared with previous conductive hydrogels, this work will provide a novel pathway to fabricate nanocomposite hydrogels with self-healing, self-adhesive, strain sensitive and robust mechanical properties for potential applications in wearable strain sensors, flexible electrical interconnection and human motion monitoring.